2022
DOI: 10.1039/d1nh00590a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition-driven supramolecular nanoassembly of a hydrophobic uracil prodrug and hydrophilic cytarabine for precise combination treatment of solid and non-solid tumors

Abstract: The reduction sensitive supramolecular nanoassembly was based on U-SS-DOX and Ara-C specific molecular recognition. The drug release in the supramolecular nanoassembly was triggered and controlled in tumor cells with low pH and excessive GSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They can also pass through the BBB into the brain tissues, inhibiting acetylcholinesterase [ 32 ]. Additionally, uracil conjugates with pharmacophores, such as DOX, and demonstrates promising outcomes in terms of cancer cell selectivity and targeted drug delivery [ 33 , 34 , 35 ]. Polyvinyl alcohol (PVA) was applied as an additional emulsifier of the nanoemulsion due to such characteristics as biodegradability, biocompatibility, and nontoxicity [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can also pass through the BBB into the brain tissues, inhibiting acetylcholinesterase [ 32 ]. Additionally, uracil conjugates with pharmacophores, such as DOX, and demonstrates promising outcomes in terms of cancer cell selectivity and targeted drug delivery [ 33 , 34 , 35 ]. Polyvinyl alcohol (PVA) was applied as an additional emulsifier of the nanoemulsion due to such characteristics as biodegradability, biocompatibility, and nontoxicity [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytarabine (Ara-C), a milestone chemotherapeutic agent, has been applied for the treatment of acute myeloid leukemia (AML) and other hematological malignancies over the past few decades . It can also be used for better of solid tumors in combination with other anticancer agents due to its rapid blood clearance. , In recent studies, Ara-C has been reported to possess immunomodulatory properties instead of the direct induction of anticancer immune responses, , suggesting that the immunological potential of Ara-C can be utilized as a means of promoting antitumor immunity in conjunction with other therapeutics, such as PDT. However, to date, to our knowledge, there is no report of the combination of Ara-C and photosensitizers for chemo-photodynamic therapy and subsequent immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…[46] Yet, despite the expansion of various strategies to design H-bonded biomaterials, the investigation of nanomedicine within such platform opposing the ordering effects via H-bonding forces is a newly emerging and extremely promising field. [47][48][49] Considering their outstanding potential in clinical research and translation, H-bonded nanomedicine has attracted the growing attention from synthetic chemists, materials scientists, biologists and physicians. [50] Several outstanding reviews have been reported in the field of supramolecular nanotheranostics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 46 ] Yet, despite the expansion of various strategies to design H‐bonded biomaterials, the investigation of nanomedicine within such platform opposing the ordering effects via H‐bonding forces is a newly emerging and extremely promising field. [ 47–49 ]…”
Section: Introductionmentioning
confidence: 99%